Osteoarthritis treatment - the newer treatment options - Devaraj, Navin Kumar (Fortune Journal, 2019)
Osteoarthritis of the knee is a common condition in the elderly. However, active participation in sports and trauma may also lead to premature osteoarthritis. This case report looks at a 60 years old woman who had severe osteoarthritis of her knees and what treatment options were helpful for her.